Reaction sintering of rhabdophane into monazite-cheralite Nd1-2xThxCaxPO4 (x = 0 – 0.1) ceramics. Issue 3 (March 2020) - Qin, Danwen; Mesbah, Adel; Lautru, Joseph; Szenknect, Stéphanie; Dacheux, Nicolas; Clavier, Nicolas
Abstract: The direct sintering of Nd1-2x Cax Thx PO4 ·nH2 O rhabdophanes (x = 0 – 0.1) was achieved for the first time resulting in homogeneous high-density monazite-cheralite pellets. Thanks to their large specific surface area, rhabdophane precursors led to a lower shrinkage temperature compared to samples synthesized through solid-state reactions. The associated activation energy was found between 360 ± 90 and 530 ± 90 kJ.mol −1, depending on the thorium incorporation. Meanwhile, sintering map was built up, showing that densification predominated for T ≤ 1200 °C. Conversely, the complete densification took place at 1400 °C concomitantly to grain growth and elimination of open porosity. Moreover, Th-Ca coupled substitution seemed to inhibit both densification and grain growth as the average grain size dropped down one order by one order of magnitude between x = 0.0 and x = 0.1. However, these differences did not affect microhardness, which reached 4.9 ± 0.8 GPa whatever the chemical composition tested.